The Intersection of Precision Medicine, Wearable Technology, and Data Analytics for Transforming Healthcare (The Peerian Journal, 2024)
Nowadays, thanks to precision medicine, we can address a lot of problems, such as improving patients' outcomes, implementing cost-effective healthcare, and customizing healthcare, all of which lead to a higher quality of life. However, there are a number of challenges that will need to be addressed before cryptocurrencies can be widely used. These include creating regulatory tokens for new technologies, securing data storage and protection on servers, and finding reliable alternative power sources for wearable devices. In this study, we lay out the many ways in which data analysis, wearable technologies, and precision medicine are shaping the future of healthcare. We talk about the current problems, new features, and good effects of these technologies. Patientcentered healthcare solutions have the potential to be greatly enhanced by incorporating these technologies into the process. In order to overcome these restrictions and embrace new possibilities for individualized health care, it is crucial to enhance power harvesting and storage equipment and create soft and flexible tools for wearable devices.